Lessons between apprentices. Vertical structure in the teaching of architecture - Alarcón González, Luisa; Montero-Fernández, Francisco (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
The teaching of architectural projects structured in vertical workshops, in which students from different years have shared teaching, has been a formula adopted in different schools and historical periods, from the Bauhaus in Germany to the present time. This educational organisation constituted the fundamental structure of the teaching of projects in the School of Architecture of Seville from the 1975-76 to the 1994-95 academic year. This system generated important synergies between teachers and students, especially significant between the students themselves who learned not only from the teacher, but also from their higher level classmates, establishing a learning structure similar to that of craft workshops, facilitating the initiation into a new practice, such as that of artistic creation, improving collaborative work and intergenerational relations.